Transcriptome and Metabolome Analyses Reveal High-Altitude Adaptation Mechanism of Epididymis Sperm Maturation in Tibetan Sheep - Yijian Li; Yanan Yang; Binyan Yu; Rong Gao; Xinrong Wang (Animals)
In this study, the epididymal histology, caepididymal sperm physiological parameters, serum reproductive hormones, and antioxidant enzyme SOD levels of Tibetan sheep at a 2500 m and 3500 m altitude were compared by using a combination of transcriptome and metabolomics methods. This was conducted to investigate the effects of a high-altitude environment on spermatogenesis and the maturation of Tibetan sheep. The results showed that compared to the low-altitude group, the high-altitude group had a smaller epididymal lumen, thicker epididymal wall, significantly decreased sperm survival rate, and significantly increased sperm deformation rate, but no difference in sperm motility and sperm respiratory intensity. With increasing altitude, Tibetan sheep showed a decreasing trend in serum reproductive hormones (FSH and T), while the antioxidant enzyme SOD activity was significantly reduced. Transcriptomic analysis revealed 139 differentially expressed genes in the Tibetan sheep epididymis under high-altitude conditions. The SYCP2 gene is involved in multiple biological processes related to reproduction and plays an important role in the regulation of epididymal function and sperm quality in Tibetan sheep. Genes like ADCYAP1R1, CABP2, CALN1, and ATP6V1B1 can help maintain sperm viability and maturation by regulating the cAMP signaling pathway, calcium ion homeostasis, and cellular signaling. Metabolomic analysis found that the high-altitude group had increased adenosine content and decreased prostaglandin I2 content in the epididymis. These metabolites are involved in spermatogenesis, motility, fertilization, and early embryonic development. The integrated omics analysis suggests that Tibetan sheep adapt to the high-altitude hypoxic environment by regulating cAMP signaling pathway genes like ADCY and PRKACA, as well as metabolites like adenosine and prostaglandin I2, to maintain epididymal function and sperm motility. These genes and metabolites play an important role in maintaining normal epididymal function and sperm motility at high altitudes.